Ambrisentan for treatment of inoperable chronic thromboembolic pulmonary hypertension (CTEPH). (May 2019) - Escribano-Subias, Pilar; Bendjenana, Hakim; Curtis, Paula S.; Lang, Irene; Noordegraaf, Anton Vonk
This multicenter, randomized, double-blind, placebo-controlled study assessed ambrisentan or placebo in patients with inoperable chronic thromboembolic pulmonary hypertension. Futility of enrollment led to early termination. Trends of improvement in favor of ambrisentan versus placebo in the primary and some secondary endpoints were observed; adverse event profiles were similar between groups.